Controllable synthesis of 3D hierarchical bismuth compounds with good electrochemical performance for advanced energy storage devices1. Issue 64 (12th July 2015) - Sun, Jinfeng; Wang, Jinqing; Li, Zhangpeng; Yang, Zhigang; Yang, Shengrong
<x xml:space="preserve">Abstract</x> 3D hierarchical bismuth (Bi)-based compounds with controllable sizes and morphologies exhibit high specific capacitance and superior rate capability.